Measuring children activity repertoire: is the paediatric activity card sort a good tool for Brazilian therapists?/Medindo o repertório de atividades de crianças: paediatric activity card sort é uma boa ferramenta para terapeutas ocupacionais brasileiros? - Pontes, Tatiana Barcelos; Silva, Bruna Mesquita; Sousa, Jaqueline; Almeida, Pedro Henrique Tavares Queiroz de; Davis, Jane; Polatajko, Helene (Cadernos Brasileiros de Terapia Ocupacional, 2016)
Introduction: The primary Brazilian occupational therapists goal is to enable their clients to participate in the activities of everyday life. Thus, it is important that therapists have tools that capture their clients’ activities repertoires. The Paediatric Activity Card Sort (PACS) is a client-centred tool designed to capture the activity repertoire of children. However, the PACS is based on the activities of Canadian children, leading to questions regarding its use in other countries. Objective: To determine the acceptability and applicability of the PACS with Brazilian children. Method: Sixty children between 5 and 14 years participated in a descriptive cross-sectional study. A questionnaire was used to gather sociodemographic information. Behavioural observations were used to judge the acceptability of the PACS. Item responses and their relation to sociodemographic variables were used to examine applicability. Descriptive statistics were used to describe demographics and item responses. Differences in the PACS scores between gender, race, presence of siblings, parents educational levels and marital status were assessed using non-parametric statistics. Results: Reported participation in PACS activities ranged from 95.7% (personal care) to 15.1% (sports). Eleven PACS activities had a participation rate of less than 10% and a number of new activities, not included in the PACS, were identified. Differences were found among gender and presence of siblings. Conclusion: With adjustments for the Brazilian context the PACS can be a useful tool to capture children activity suggesting the potential usefulness of a Brazilian PACS.